Remanent magnetization of maghemitized basalts from Krafla drill cores, NE-Iceland - Oliva-Urcia, Belén; Kontny, Agnes (Studia Geophysica et Geodaetica)
We investigated the natural remanent magnetization (Jr) of hydrothermally altered basalts from two drill cores KH1 (200 m) and KH3 (400 m) situated at the rim of the Krafla caldera in NE Iceland, where a geothermal field (>150°C) is still active. Low temperature oxidation along with mineral reactions in the chlorite zone (<350°C) is the prevailing cause for the maghemitization and a strong decrease of Jr to occur in our study. Despite a significant decrease of Jr with respect to fresh basalts in surface outcrops of the same area, the stepwise demagnetization analyses of Jr show the presence of a stable magnetic component with the expected inclination of 77° in Iceland. Because the alteration temperature (<350°C) is above the Curie temperatures of most of the original titanomagnetite (40°–350°C), we suggest that a normal direction of remanence is chemically acquired during the low temperature alteration. We observed only one reliable negative inclination at 293.2 m in the KH3 core, which we rather interpret to be acquired during a geomagnetic excursion with reverse polarity than caused by a self-reversal mechanism. Belén Oliva-Urcia, Agnes Kontny. Obsahuje seznam literatury